2021
DOI: 10.7759/cureus.16011
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Mastoid Parameters for Sexual Differentiation in North Indian Population

Abstract: Introduction: Morphometric differences of several bones form the basis of sexual differentiation. The mastoid triangle has been widely used as a predictor of sexual differentiation. However, the radiographic measurements of the mastoid triangle, which form the clinical alternative of this parameter, have not been studied in the North Indian population. Therefore, we analyzed skull radiographs of live subjects to investigate the effectiveness of the radiographic mastoid triangle in sex determination.Methods: On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…where ρ o is the organic matter density in g/cm 3 , ρ mi is the average density of grain and pore fluid in g/cm 3 , R ρ is the ratio of the organic matter to organic carbon in weight percentage. Passey et al 55 suggested an easy-to-use model for TOC prediction, as summarized in eqs 3 and 4. Currently, this model is widely used for evaluating the unconventional resources reserve.…”
Section: Introductionmentioning
confidence: 99%
“…where ρ o is the organic matter density in g/cm 3 , ρ mi is the average density of grain and pore fluid in g/cm 3 , R ρ is the ratio of the organic matter to organic carbon in weight percentage. Passey et al 55 suggested an easy-to-use model for TOC prediction, as summarized in eqs 3 and 4. Currently, this model is widely used for evaluating the unconventional resources reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they concluded that the parameters were nearly the same on both sides for both genders. [16] Passey et al [2] determined A-AMP distance as an average of 50.00±9.75 mm in males and 49.84±6.97 mm in females over 100 radiographs (p<0.001). Helmy et al [17] revealed that the A-AMP distance was 5.21 cm (right), 5.24 cm (left) in males, and 4.72 cm (right), 4.80 cm (left) in females.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of Asterion to the MT have been conducted in previous studies. [1][2][3][5][6][7]13,14] The distance between Asterion and the apex of the mastoid process (A-AMP) was revealed as 49.20±4.68 mm by Day et al, [13] 49.70±4.80 mm by Martinez et al, [14] 47.89± 3.72 mm for the right side and 47.62 ± 2.87 mm for the left side by Mwachaka et al, [3] 49.1±5.4 mm by Ucerler and Govsa, [1] 51.53±4.97 mm by Galindo-de Leon et al, [5] 43.65±6.75 mm for the left side and 45.01± 6.04 mm for the right side by Akkaflo¤lu et al, [6] 48.7±0.56 mm for the left side by Çal›flkan et al [7] in various populations. However, Kemkes and Göbel [15] found the A-AMP as 49.4±5.1 mm (right), 49.4±5.5 mm (left) in females, and 50.2±4 mm (right), 50.5±4.8 mm (left) in males in German population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skull is the second-best predictor of sex determination after the pelvis [3,4] . Several cranial metric parameters have been studied for age and sex determination, including cranium maximum length and breadth, bizygomatic distance, mastoid process and foramen magnum dimensions, and paranasal sinuses measurements [5][6][7][8][9][10][11] . The crucial point is the ability to analyze bones in fragmented or extensively disfigured states, so it is essential to use denser bones that are frequently retrieved intact [12] .…”
Section: Introductionmentioning
confidence: 99%